Drivers of FDI inflows in Africa: do trade openness, market size, and institutional quality matter? - Abdikafi Hassan Abdi; Ibrahim Abdukadir Sheik-Ali; Farhia Hassan Mohamed; Salman Sh. Adem Mohamoud (Cogent Economics & Finance)
Foreign direct investment serves as a cornerstone for economic development, particularly in lower- and middle-income countries, where it brings crucial capital, technology, and expertise. Despite institutional challenges in many African nations, there is controversy over the effects of macroeconomic variables and institutional quality on FDI flows within diverse economic landscapes. Given the persistent challenges faced by Africa’s least FDI-receiving countries, it is essential to focus on understanding the specific factors that hinder or promote FDI in these nations. Therefore, this study investigates the impact of macroeconomic stability and institutional quality on attracting foreign capital in 24 African economies from 2004 to 2022. Utilizing the pooled mean group (PMG) method, validated by the fully modified ordinary least squares (FMOLS) cointegration technique, the study findings indicate that GDP per capita and domestic investment positively enhance FDI in the long run. This highlights the importance of economic growth and local investment in attracting foreign investment. Institutional quality has also emerged as a significant long-run determinant of FDI. Additionally, currency depreciation is identified as crucial for sustaining increased FDI inflows in African countries. Conversely, trade openness and high inflation hamper FDI inflows in the long-run. Considering these findings, policymakers should focus on maintaining economic stability, improving governance, balancing trade openness, and stabilizing exchange rates.